Pengaruh Kompetensi Kerja, Disiplin Kerja Terhadap Kinerja Pegawai melalui Kompensasi Kerja sebagai Variabel Mediasi (Studi Kasus Pada PT Sun Star Prima Motor Tajur - Aulia Reza Apriani (2022)
"This study is a quantitative study that aims to determine whether there is an influence between work competence and work discipline through work compensation as a mediating variable on employees of PT Sun Star Prima Motor Tajur. The study used a total of 65 respondents, with a saturated sampling technique. The analysis technique used is path analysis and data processing which is carried out through SmartPLS 3.0. the results of the test obtained (1) work competence has a positive and significant effect on the performance of employees of PT Sun Star Prima Motor Tajur. (2) work discipline has a positive and significant effect on the performance of PT Sun Star Prima Motor Tajur employees. (3) work competence has a positive and significant effect on the performance of employees of PT Sun Star Prima Motor Tajur mediated by work compensation. (4) work discipline has a positive and significant effect on the performance of employees of PT Sun Star Prima Motor Tajur which is mediated by work compensation (5) work compensation has a positive and significant effect on the performance of employees of PT Sun Star Prima Motor Tajur." "Keywords: Work Competence, Work Discipline, Work Compensation and Employee Performance."